Brand building a "premie" care product line : Nurtured by Design - Thomas, Sujo; Suggala, Sushmita (London : NeilsonJournals Publishing, 2020)
This case portrays the journey of Dr. Jackson, who after her own stressful experience of giving birth prematurely ("premie"), established the company Nurtured by Design (NBD) in 2001. The first brand was launched in 2004 followed by the launch of further brands in the coming years. The products were designed ergonomically and aimed at helping hospital staff, mothers and parents provide essential care and comfort for prematurely born babies. After a successful launch, NBD had to then decide on the next phase and manage growth carefully by meeting certain key targets. In 2018, NBD undertook a rebranding exercise for all the brands under its portfolio. It was crucial for the company to evaluate the growth opportunities and prepare a strategy to create further brand awareness. A priority was always to strike a balance between the social and business goals. However an extended focus on social outcomes could lead to losses, whereas focusing heavily on business outcomes would be a deviation from Dr. Jackson's dream of creating a better world for prematurely born babies across the world. NBD had to overcome these and other challenges to further build and develop a successful brand while facing a complex business environment both domestically and internationally.
Originally Published InThomas, S., & Suggala, S. (2020). Brand Building a "Premie" Care Product Line: Nurtured by Design. Journal of International Business Education, 15(1), 317-330. JIBE15-0CS2.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Branding (Marketing) -- Case studies; Premature infants -- Home care -- Case studies; Premature infants -- Hospital care -- Case studies